ANALISIS PENGARUH SENSITIVITAS POLITIK TERHADAP BIAYA POLITIK (Studi Empiris pada Penyedia Barang/Jasa yang Terdaftar di Bursa Efek Indonesia) - Ika Pratiwi; Aditya Septiani (Diponegoro Journal of Accounting, 2015)
The aim of this research is to examine the influence of political sensitivity that is reviewed with the high visibility and the importance of contracts to the firm. Firm size, profitability, leverage, capital intensity, inventory intensity used as control variable. The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2013. Sampling method used is purposive sampling. Company criteria used is listed company in BEI 2013 for all industrial sectors except the agriculture sector and the financial sector. A company that only sampled must have a government contract in 2013 and value of the income before tax was positive in 2013. Total data of this study is 90 data. There are not samples that include outlier should be excluded from samples of observation. Simple regression used to be analysis technique. The empirical result of this study show that political sensitivity review by the high visibility have positively significant influenced on political cost. While the political sensitivity that is reviewed by the importance of the contract did not show significant results.